Sleep Duration and Excessive Daytime Sleepiness Are Associated with Obesity Independent of Diet and Physical Activity - Maugeri, Andrea; Medina-Inojosa, Jose R; Kunzova, Sarka; Agodi, Antonella; Barchitta, Martina; Sochor, Ondrej; Lopez-Jimenez, Francisco; Geda, Yonas E; Vinciguerra, Manlio (Nutrients, 2018)
In the European Union, Czech Republic ranks 3rd and 6th for the incidence of obesity and cardiovascular diseases, respectively. Worldwide, short sleep duration and excessive daytime sleepiness (EDS) characterize obese subjects, which in turn exhibit scarce physical activity and unhealthy diet. We aimed to understand the relationship between irregular sleep patterns, obesity and lifestyle factors, such as diet and physical activity, in a vulnerable Czech population. 1482 members of the Kardiovize cohort, a random sample of the Czech urban population, were included in a cross-sectional study. Exposure variables included self-reported sleep duration and EDS, assessed by the Epworth Sleepiness Scale. Primary outcomes were BMI and waist-to-hip ratio or prevalence of obesity and central obesity. Covariates included physical activity and diet. Associations and interactions between variables were evaluated using logistic regression analyses. After adjustment for covariates, short sleep duration (<7 h) was associated with greater odds of overweight (BMI > 25; OR = 1.42; 95%CI = 1.06⁻1.90; p = 0.020) and obesity (BMI > 30; OR = 1.40; 95%CI = 1.02⁻1.94; p = 0.047), while EDS was associated with greater odds of central obesity (OR = 1.72; 95%CI = 1.06⁻2.79; p = 0.030), independent of diet and physical activity. However, due to the cross-sectional nature of our study, further prospective, large-scale studies are needed to evaluate the etiological link and causality between sleep disturbances and obesity.
Keywords: nadváha; Odds Ratio; Sleep Wake Disorders; Waist-Hip Ratio; zpráva o sobě; lidé; Middle Aged; Adult; Sleep; cvičení; poruchy spánku a bdění; Obesity; central obesity; odds ratio; Wakefulness; stravovací zvyklosti; Female; Exercise; Feeding Behavior; poměr pasu a boků; Body Mass Index; diet; Humans; index tělesné hmotnosti; průřezové studie; bdění; physical activity; Overweight; obezita; Cross-Sectional Studies; Česká republika; dieta; abdominální obezita; Obesity, Abdominal; lidé středního věku; kohortové studie; logistické modely; mužské pohlaví; Cohort Studies; overweight; Sedentary Behavior; Diet; Czech Republic; ženské pohlaví; Logistic Models; Male; spánek; Self Report; dospělí; body mass index; sedavý životní styl